43.0k views
2 votes
Which of the following is equivalent to

Which of the following is equivalent to-example-1
User Ashanti
by
5.3k points

2 Answers

2 votes

Answer:

C

Explanation:

Using the rules of radicals


√(a) ×
√(b)
√(ab) and


√(a) ×
√(a) = a

Given


(√(2a) )/(√(3) )

Multiply the numerator/ denominator by
√(3)

=
(√(2a) )/(√(3) ) ×
(√(3) )/(√(3) )

=
(√(2a(3)) )/(3) =
(√(6a) )/(3)

User Foxlab
by
5.1k points
6 votes

Answer:

C

Explanation:

Multiply the numerator and denominator by sqrt 3 to rationalize the denominator.


(√(2a))/(√(3)) * (√(3) )/(√(3) ) = (√(6a) )/(3)

User Sharmi
by
4.9k points